HUBUNGAN ANTARA KUALITAS TIDUR DENGAN DEPRESI PADA LANSIA WANITA DI KOMUNITAS DAHLIA SENJA LIMO DEPOK - Fildzah Alifah Maulani (2023)
Background : Elderly is an advanced stage of a life process. The elderly have a period where there is a decline in the function of the body's organs anatomically, physiologically and psychologically. Sleep quality is a person's satisfaction with sleep. Depression is a common mental disorder. The purpose of this study was to determine the relationship between sleep quality and depression levels in the elderly Dahlia Senja community. Design :The design of this study used a cross-sectional method based on the results of measuring sleep quality using the Pittburgh Sleep Quality Index (PSQI) questionnaire and measuring depression levels using the Geriatric Depression Scale (GDS) questionnaire. The sample in this study were the elderly in the Dahlia Senja Limo Depok Elderly Community, totaling 40 samples. By using the Chi-Square test data analysis. The results: This study says that 90% of the elderly have poor sleep quality and 55% are found to be elderly with non-depressive conditions and 35% of the elderly have mild depressive disorders. The value value for the elderly is 0.368 > 0.05. It can be concluded that there is no significant relationship between sleep quality and depression in elderly women in the Dahlia Senja Senja Limo Depok Elderly Community. Where poor sleep quality tends to have a level of risk of depressive symptoms in the elderly.